Geopolitical Risk, Economic Policy Uncertainty, and Islamic Stock Returns - Nadia Arisanti; Mawardi, Imron (Universitas Airlangga, 2025)
This study aims to examine the short-term and long-term effects of geopolitical risk and economic policy uncertainty on Sharia stock returns in the Jakarta Islamic Index (JII) during the period from January 2018 to December 2023. This research employs a quantitative approach using the Vector Error Correction Model (VECM) analysis technique. The results indicate that geopolitical risk has a negative and significant impact in both the short and long term. Meanwhile, economic policy uncertainty does not have a significant effect in the short term but has a negative and significant impact in the long term. This study also incorporates control variables, including global oil prices, global gold prices, exchange rates, and inflation. All control variables significantly influence Sharia stock returns in JII in the long term. In the short term, however, only global oil prices and exchange rates have a significant impact on Sharia stock returns in JII.